Education and Youth Development: Problems and Prospects (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Education plays a key role in shaping personality, professional development, and social adaptation of youth. This article analyzes the modern challenges faced by young people in the educational process and examines innovative approaches aimed at improving the quality of education. Special attention is given to digitalization, inclusivity, and the development of 21st-century skills.